أثر الأتمته على تحسين قيادة المؤسسات الاجتماعية - دحبج، سالم حمد سالم حمد (محمد قاسمي, 2023)
تهدف هذه الدراسة الوقوف عند مفهوم الأتمته وتطورها كمفهوم جديد داخل حقل العلوم الإدارية، وكذلك الوقوف عند دورها في تحسين قيادة المؤسسات الاجتماعية، وفهم طبيعة العلاقة بين توافر متطلبات أتمتة العمليات الإدارية والرفع من جودة المؤسسات الاجتماعية، وكذلك التعرف على المعوقات والتحديات التي تحول دون تفعيل دور الأتمته في تحسين قيادة المؤسسات الاجتماعية. This study aims to examine the concept of automation and its development as a new concept within the field of administrative sciences. as well as to examine its role in improving the leadership of social institutions, and to understand the nature of the relationship between the availability of requirements for the automation of administrative processes and raising the quality of social institutions, as well as to identify the obstacles and challenges that prevent activating the role of automation. Automation in improving the leadership of social enterprises.
Keywords: المؤسسات الاجتماعية -- العلوم الإدارية -- تكنولوجيا المعلومات